FROM OCCUPATIONAL SAFETY TO COMPREHENSIVE SECURITY: STRATEGIES FOR INTEGRATING CIVIL DEFENSE INTO CORPORATE MANAGEMENT SYSTEMS - Pogrebnyak, V. G.; Perkun, I. V.; Vyshnikina, O. V.; Pogrebnyak, A. V. (Systems and Technologies, 2025)
The article substantiates an urgent scientific and practical problem that has arisen due to the full-scale war in Ukraine – the fundamental inadequacy of traditional corporate safety management systems in the face of new hybrid threats. It is proven that the classic model, where occupational safety (OS) and civil defense (CD) function as two parallel, weakly integrated sys- tems, is outdated and incapable of providing an adequate level of protection for personnel and assets of enterprises, which have become potential targets for military attacks. Existing occupational safety management systems, built on peacetime standards (e.g., ISO 45001), are focused on preventing unintentional incidents and lack the tools to counter deliberate external impacts. The purpose of the article is to develop scientifically-backed strategies for integrating civil defense functions into corporate occupational safety management systems to create a unified, comprehensive enterprise security model adapted to the conditions of hybrid threats. Based on an analysis of classical concepts (Safety-I, Safety-II, Resilience Engineering) and the legal frame- work of Ukraine, a key gap has been identified – the absence of a holistic model for managing all types of security risks at the corporate level. The scientific novelty of the work lies in the proposal of a conceptual model for an integrated comprehensive security management system (CSMS) for the first time. Unlike existing approaches, this model synthesizes OS and CD into a single management cycle ("analysis – prevention – response – recovery"), based on five key principles: unity of command, pro- activity, total risk orientation (including military risks), human-centricity, and continuity. This approach allows for a transition from the outdated dichotomy of "internal/external threats" to a single management loop for all identified risks, regardless of their origin. The practical significance lies in the development of four groups of specific integration strategies: legal-regulatory (creating a unified Comprehensive Security Regulation), organizational-managerial (forming a single security center), technical-technological (integrating alert and monitoring systems), and socio-psychological (conducting comprehensive training and providing psychological support). The proposed strategies can serve as a roadmap for managers of Ukrainian enterprises to reform existing systems, enhance personnel protection, ensure the resilience of business processes, and save human lives under martial law.